Update on Medication-overuse Headache - De Felice, Milena (2011)
Medication-overuse headache (MOH) is a syndrome that can develop in migraineurs after overuse of antimigraine drugs, including opiates and triptans especially. MOH manifests as increased frequency and intensity of migraine attacks and enhanced sensitivity to stimuli that elicit migraine episodes. Although the mechanisms underlying MOH remain unknown, it is hypothesized that repeated use of antimigraine drugs could elicit increased headache attacks as a consequence of neuronal plasticity that may increase responsiveness to migraine triggers. Preclinical studies show that exposure to either opiates or triptans can induce pronociceptive neuroadaptive changes in the orofacial division of the trigeminal ganglia that persist even after discontinuation of the drug treatment. Additionally, medications can elicit increased descending facilitatory influences that may amplify evoked inputs from trigeminal afferents leading to behavioral hypersensitivity reminiscent of cutaneous allodynia observed clinically. Importantly, enhanced descending facilitation may manifest as an inhibition of diffuse noxious inhibitory control. Persistent, pronociceptive adaptations in nociceptors as well as within descending modulatory pathways thus may jointly contribute to the development of MOH.